STRATEGI PENGEMBANGAN AGRIBISNIS PADI MELALUI PEMBANGUNAN RICE ESTATE DI KABUPATEN KUBU RAYA - Syahrizal, Budi; Yusra, Abdul Hamid A.; Gafur, Sutarman (Jurnal Social Economic of Agriculture, 2013)
Budi Syahrizal "Rice Agribusiness Development Strategy Development Through Rice Estate in Kubu Raya District", under the guidance of Ir . A. Hamid A. Yusra, MS and Dr. Ir. H. Sutarman Gafur, M.Sc. The research aims to : 1. Knowing the real rice management by Kubu Raya District Government in increasing rice production. 2. Identifying factors external environment into opportunities and threats management of real rice and internal environmental factors are the strength and weaknesses of the management of real rice. 3. Formulate alternative strategies that can be implemented according to the manager of the rice area real environmental conditions. 4. Analyzing priority management strategies that can be implemented in accordance with the environmental conditions of real rice area . Benefits of this research are : 1. As an input for the management of real rice in Kubu Raya District to be considered in carrying on their business in the face of environmental changes occur real rice. 2. This study is also expected to be material information for the various parties involved in the management of real rice to prepare measures that can improve the production and productivity of rice in order to self-sufficiency and food security in Indonesia , particularly the Kubu Raya District immediately reached. 3. As for the academics, hopefully this study can be material information, comparisons and references for further studies. The research was conducted in the village of Kuala Foreman A B District Overseer Kuala Kubu Raya district of West Kalimantan Province and held for about 2 months. Method used was a survey method and included in the descriptive study. The population in this study are all stakeholders involved in the system of rice agribusiness. The sampling technique used was purposive sampling, which determine directly or selecting respondents deliberately . The results of this study are : SWOT analysis matrix shows the internal - external strategic factors obtained is : SO the value of 3,2748 , with a value of 3,0448 ST, WO and WT with a value of 2.5888 with a value of 2.3588. Thus rice agribusiness development strategy through a in Kubu Raya District can use the SO strategy. Keywords : Strategy, Sustainability, Rice, Rice Estate, SWOT .